Bone targeting nanocarrier-assisted delivery of adenosine to combat osteoporotic bone loss. (June 2021) - Hoque, Jiaul; Shih, Yu-Ru V.; Zeng, Yuze; Newman, Hunter; Sangaj, Nivedita; Arjunji, Neha; Varghese, Shyni
Abstract: Extracellular adenosine has been shown to play a key role in maintaining bone health and could potentially be used to treat bone loss. However, systemic administration of exogenous adenosine to treat bone disorders remains a challenge due to the ubiquitous presence of adenosine receptors in different organs and the short half-life of adenosine in circulation. Towards this, we have developed a bone-targeting nanocarrier and determined its potential for systemic administration of adenosine. The nanocarrier, synthesized via emulsion suspension photopolymerization, is comprised of hyaluronic acid (HA) copolymerized with phenylboronic acid (PBA), a moiety that can form reversible bonds with adenosine. The bone binding affinity of the nanocarrier was achieved by alendronate (Aln) conjugation. Nanocarriers functionalized with the alendronate (Aln-NC) showed a 45% higher accumulation in the mice vertebrae in vivo compared to those lacking alendronate molecules (NCs). Systemic administration of adenosine via bone-targeting nanocarriers (Aln-NC) attenuated bone loss in ovariectomized (OVX) mice. Furthermore, bone tissue of mice treated with adenosine-loaded Aln-NC displayed trabecular bone characteristics comparable to healthy controls as shown by microcomputed tomography, histochemical staining, bone labeling, and mechanical strength. Overall, our results demonstrate the use of a bone-targeting nanocarrier towards systemic administration of adenosine and its application in treating bone degenerative diseases such as osteoporosis. Graphical abstract: Image 1